Gamelan Kakelentingan sebagai Representasi Identitas Budaya Masyarakat Bali: Studi Etnomusikologi di Desa Apuan, Baturiti, Tabanan - Kadek Agung Sari Wiguna; Pande Putu Yogi Arista Pratama (Mahesa Research Center, 2026)
Gamelan Kakelentingan is one of Bali’s traditional music ensembles whose existence is local in nature and has received limited academic attention. This article aims to examine the musical form and structure, socio-cultural functions, and aesthetic values of Gamelan Kakelentingan as a representation of the cultural identity of its supporting community. This study employs a qualitative approach, with data collected through observation, interviews, and literature review. Data analysis is conducted using a descriptive-analytical method by relating field findings to concepts in karawitan studies and ethnomusicology. The findings reveal that Gamelan Kakelentingan possesses a simple yet well-organised musical structure, with performance patterns that are contextual and adaptive to social and ritual functions. Socially and culturally, this ensemble functions as a medium for collective interaction, a means of intergenerational transmission of cultural values, and a marker of community identity. The aesthetic value of Gamelan Kakelentingan is reflected in the harmony between sound, function, and performance context, emphasising collective harmony rather than technical complexity. This study confirms that Gamelan Kakelentingan makes a significant contribution to the corpus of Balinese karawitan and should be understood as a living and dynamic cultural practice that remains relevant within the contexts of preservation and arts education.